Interleukin-37 Suppresses the Function of Type 2 Follicular Helper T in Allergic Rhinitis - Xi Luo; Yanhui Wen; Xiangqian Qiu; Lifeng Zhou; Qingxiang Zeng; Wenlong Liu (Biomedicines)
Background: Allergic rhinitis (AR) is triggered by immunoglobulin E (IgE)-mediated immune responses to airborne allergens. Recent studies highlight the pivotal role of T follicular helper 2 (Tfh2) cells in IgE production. Interleukin-37 (IL-37) has emerged as an intrinsic modulator of innate immunity and inflammatory processes. We aimed to investigate the regulatory effect of IL-37 on Tfh2 cells in the pathogenesis of AR. Methods: Blood samples were collected from AR patients and controls. The IL-37 levels and the frequency of Tfh2 cells were detected by enzyme-linked immunosorbent assay (ELISA) and flow cytometry, respectively. The isolated Tfh2 cells were cultured or cocultured with naive B cells. The regulatory effects of IL-37 on Tfh2/B cells were assessed using ELISA, quantitative real-time polymerase chain reaction (qRT-PCR). Mouse models of ovalbumin (OVA)-induced AR were established to explore the effect of IL-37 in vivo. Results: IL-37 suppressed the production of IL-4 and IL-21 by Tfh2 cells and downregulated C-X-C chemokine receptor type 5 (CXCR5) and B-cell lymphoma 6 protein (Bcl6) mRNA expression while upregulating B lymphocyte-induced maturation protein 1 (Blimp1) and signal transducers and activators of transduction5 (STAT5) mRNA. IL-37 decreased IgE production by B cells significantly, and the addition of anti-IL-18 receptor α alleviated this effect. In mouse models, IL-37 reduced nasal rubbing, sneezing, eosinophil counts, OVA-specific IgE, and Tfh2 proportions. Conclusions: IL-37 plays a crucial role in modulating Tfh2 cell responses in AR, suggesting a potential therapeutic target for this condition.